Promoting agri-food systems resilience through ICT in developing countries amid COVID-19 - Alam, GM Monirul; Khatun, Most Nilufa; Sarker, Md Nazirul Islam; Joshi, Niraj Prakash; Bhandari, Humnath (Frontiers in Sustainable Food Systems, 2023)
An increasing body of literature has demonstrated COVID-19's harmful impact on agri-food systems, which are a major source of livelihood for millions of people worldwide. Information and communication technology (ICT) has been playing an increasing role in enhancing agri-food systems' resilience amid COVID-19. In this study, the PRISMA approach was employed to perform a systematic review of literature on the overall impact of COVID-19 on agri-food system networks and ICT’s role in enhancing agri-food system resilience in developing countries. This study reveals that COVID-19 has posed abundant obstacles to agri-food systems actors, including a lack of inputs, technical support, challenges to selling the product, transportation barriers, and low pricing. These impediments result in insufficient output, unforeseen stock, and revenue loss. COVID-19's restrictions have caused a significant food deficit by disrupting the demand and supply sides of the agri-food system networks. A high number of small-scale farmers have had to deal with food insecurity. As a result of the cumulative effects, actors in the agri-food system are getting less motivated to continue producing. This study also argues that many challenges in the agri-food systems can be overcome using ICTs, including maintaining precise farm management, product marketing, and access to production inputs. To assist stakeholders in coping with, adapting to, and building resilience in the agri-food system networks, this article emphasizes the critical need to turn to and expand the application of advanced agricultural ICTs to meet the world's growing needs for food production and to ensure the resilience and sustainability of farming systems, particularly in the face of a pandemic like COVID-19.